1986
DOI: 10.1209/0295-5075/1/7/004
|View full text |Cite
|
Sign up to set email alerts
|

Optically Monitored Melting, Supercooling and Solidification of Lead Aggregates Embedded in a Dielectric Matrix

Abstract: The solid ⇌ liquid transitions of lead aggregates embedded in a silicon matrix are investigated through optical measurements. A phenomenological model linking optics and thermodynamics of melting is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…In order to investigate the size dependence of the melting temperatures of nanocrystals, many experimental techniques have been used, namely differential thermal analysis and differential scanning calorimetry (Dick et al, 2002;Sheng et al, 1997;Lavc ˇevic ´& Ogorelec, 2003;Jo et al, 2011), optical reflection and transmission (Garrigos et al, 1986;Haro-Poniatowski et al, 2005), transmission electron microscopy (Xu et al, 2007;Goldstein et al, 1992), and X-ray diffraction (Wang & Zhu, 2015;Freitas et al, 2006). Although these techniques generally provide useful results, they may in some cases be subject to severe drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the size dependence of the melting temperatures of nanocrystals, many experimental techniques have been used, namely differential thermal analysis and differential scanning calorimetry (Dick et al, 2002;Sheng et al, 1997;Lavc ˇevic ´& Ogorelec, 2003;Jo et al, 2011), optical reflection and transmission (Garrigos et al, 1986;Haro-Poniatowski et al, 2005), transmission electron microscopy (Xu et al, 2007;Goldstein et al, 1992), and X-ray diffraction (Wang & Zhu, 2015;Freitas et al, 2006). Although these techniques generally provide useful results, they may in some cases be subject to severe drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed on Pb aggregates in SiO demonstrated that instead of superheating, the T m was reduced relative to the bulk. 11 While the superheating of lead crystallites on a carbon surface will depend on both size and shape. 12 Our recent results for the ''as-quenched'' and ''as-milled'' samples of Pb particles embedded in Al matrix also indicate that in order to achieve superheating, coherent or semicoherent interface must be formed.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been previously observed not only for Bi nanostructures, [27] but also for other metal nanostructures (e.g., Pb, Sn, Cd, In, and Tl). [53,54] This deviation of the cooling curve marks the temperature regime in which the Bi nanostructures are in the so-called supercooled state, without being able to initiate solidification, despite being below the nominal solidification temperature. The underlying reason for this phenomenon is the high energy barrier for the nucleation of the solid phase inside the liquid phase due to the need of formation of a solid-liquid interface.…”
Section: Understanding Switching Dynamics In Bi Metasurfaces: Tuning the On-statementioning
confidence: 99%